Effects of fresh and steammed sago with methionine and lysine supplementation in the ration on broiler performance and its abdominal fat content - Suryana Suryana (Indonesian Center for Animal Research and Development (ICARD), 2006)
An experiment has been conducted to study effects of sago inclusion in ration with methionine and lysine supplementation on broiler performance and its abdominal fat content. One hundred and eighty male broiler chicken of strain ISB-707 at the age of 7 days were randomly allocated to nine groups of experimental rations which were replicated four times (five bird each) in a completely randomized design. The treatments were; R0 (control), R1 (15.0% fresh sago), R2 (15.0% fresh sago + 0.1% methionine and 0.3% lysine), R3 (30.0% fresh sago), R4 (30.0% fresh sago + 0.1% methionine and 0.3% lysine), R5 (15.0% steamed sago), R6 (15.0% steamed sago + 0.1% methionine and 0.3% lysine), R7 (30.0% steamed sago) and R8 (30.0% steamed sago + 0.1% methionine and 0.3% lysine). The parameters recorded in this experiment were: feed intake, protein intake, energy intake, methionine intake, lysine intake, weight gain, carcass weight, carcass percentage and abdominal fat. Variables differences were examined for significances using Duncan test. Results showed that 15% steamed sago with supplementation of 0.1% methionine and 0.3% lysine significantly (P<0.05) increased the feed intake, weight gain, carcass percentage and carcass weight. Methionine and lysine supplementations decreased feed conversion ratio and abdominal fat content of broilers.Key Words: Fresh and Steamed Sago, Methionine, Lysine, Broilers